Adubação orgânica com base na taxa de mineralização de nutrientes do composto orgânico - Magalhães, Ana Caroline Messias de (2018)
The use of organic waste for the fertilization of agricultural crops has been pointed out as the most economical and sustainable way of disposing of waste produced by society. In addition to promoting nutrient cycling, the use of organic wastes as fertilizers improves the physical, chemical and biological properties of the soil. However, since the nutrient availability of these fertilizers depends on the recalcitrance of organic fertilizer and environmental conditions, there is still no precise methodology for recommending the dose to be applied. The present work aimed to evaluate the recommendation of organic fertilization from the constitution of the organic material, the nutrient mineralization coefficients. The study was developed in two phases: In the first phase, the organic compound and the soil were characterized as granulometry, pH, carbon (C) and macro and micronutrient contents. Then, the nutrient mineralization of the organic compound was quantified over the course of 63 days of incubation of the most compound soil. The results were adjusted to the exponential model for the determination of the nutrient mineralization coefficients. In the second stage, the recommendation of the organic fertilization dose was performed based on the nutrient mineralization rate N, P and K according to the equation proposed by Furtini Neto et al. (2001) modified by Silva (2008). The experiment was carried out in a completely randomized blocks with five treatments and five replications. The treatments were constituted by the standard treatment of mineral fertilization, treatment without fertilization and doses of organic compound equivalent to 100 and 200 and 300% of the amount of nutrients of the standard treatment. The equivalence between organic and mineral fertilization was calculated based on the amount of nutrients theoretically mineralized organic fertilizer. Soil nutrient content, nutrient content in leaves, yield components and yield of bean plants were evaluated. The data concerning the mineralization of N, P and K release did not fit the exponential model. The recovery of K applied in the mineral form of the soil was more efficient than the recovery of K applied in the organic form. Equivalent doses of organic and mineral P had a similar effect on the labile P content. The levels of B, Cu, Mn and K were well below the adequate levels established by the literature for cowpea. Despite this, the yields were comparable or higher than those in the literature, there was no positive correlation of these nutrients with productivity. The productivity reached in the standard treatment (mineral fertilization) was comparable to the productivity found in the treatment with organic fertilization corresponding to the nutrient in less availability.